Design and build an office network : switch configuration, wireless networking, and firewalls - Dooley, Kevin (O'Reilly, 2016)
"With Early Release video training, you get videos as they're being developed so you can take advantage of these technologies long before the official release of these titles. You'll also receive updates when significant changes are made, new chapters as they're edited, and the final video. In this Design and Build a Small Office Network course description, expert author Kevin Dooley will teach you how to design and implement secure and manageable network infrastructure. This course is designed for users that already have a general understanding of network infrastructure. You will start by learning about network design concepts, then jump into learning about switch configuration, including switch ports, Link Aggregation Control Protocol (LACP), and switch power and environment. From there, Kevin will teach you about wireless networking, including initial configuration and wireless networking with Fortinet. Finally, you will learn about firewalls, including segmentation and DMZs, implementing firewall rules, and next generation firewall features. Once you have completed this computer based training course, you will have gained a solid understanding of how to design and build a small office network."--Resource description page.